Antibacterial efficacy of Pimenta dioica (Linn.) Merill and Anacardium occidentale L. against drug resistant urinary tract pathogens - Manasa M, Yashoda Kambar, Sachidananda Swamy H.C., Vivek M.N, Ravi Kumar T.N., Prashith Kekuda T.R (Journal of Applied Pharmaceutical Science, 2013)
The aim of the present study was to determine antibacterial effect of leaf and bark extracts of Pimenta dioica (Linn.) Merill (Myrtaceae) and Anacardium occidentale L. (Anacardiaceae) against drug resistant clinical isolates of urinary tract infection viz., Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus and Enterococcus faecalis. Agar well diffusion method was employed to assess inhibitory activity of leaf and bark extracts. Among extracts, bark extract of P. dioica and leaf extract of A. occidentale exhibited high inhibitory activity. The bark extract of P. dioica showed high inhibition of clinical isolates than other extracts. Among bacteria, E. faecalis and K. pneumoniae were inhibited to high and least extent respectively. The inhibitory potential of extracts could be attributed to the presence of bioactive secondary metabolites. Isolation of inhibitory principles from crude extracts and their inhibitory activity against UTI pathogens are to be carried out.
Keywords: Pimenta dioica, Anacardium occidentale, Urinary tract infection, Agar well diffusion.